The Research on Overseas Students’ Errors of Homophone Writing - Sun, Yuqing; Liu, Yue (Journal of Sinology (วารสารจีนวิทยา), 2014)
The paper mainly studies overseas students’ errors of homophone writing from three aspects. First, it verifies three disciplines about overseas students’ errors of homophone writing. Second, it analyzes the reasons of leading to homophone writing errors. Third, it puts forward related strategies to decrease overseas students’ errors of homophone writing. This study is aiming at improving homophone teaching of overseas students.